Manajemen usaha Ayam Pedaging Jantan dan Betina dengan Penambahan Suplemen Organik Cair - Kamaludin Kamaludin; P W Dzikrillah; M F Azhoheru; Suhendrian Suhendrian; W Hardiansyah; D D Putri; G G Maradon (Politeknik Negeri Lampung, 2019)
This study aims to determine the growth of broiler chickens and analyze the feasibility of broiler farming with the addition of liquid organic supplements. Liquid organic supplements (SOC) or also called probiotics contain Lactobacillus sp, Azetobacter sp, Basiluss sp, vitamins, and minerals. SOC can increase antibodies, reduce stress levels, suppress the onset of disease, help stimulate appetite, and accelerate the growth of broiler chicken. Broilers are divided into 4 treatments female broilers without SOC, male broilers without SOC, female broilers with the addition of SOC, and treatment of male broilers with the addition of SOC. Based on the results and discussion the highest PBB is obtained by male chicken with SOC. Feasibility analysis shows that all treatments are feasible, B/C (3.11) and R/C (3.18) values of treatments added by SOC are higher than treatments without SOC.Keywords: Broiler, Feasibility Analysis, SOC